Fertilized graminoids intensify negative drought effects on grassland productivity - Kevin Van Sundert; Mohammed A. S. Arfin Khan; Siddharth Bharath; Yvonne M. Buckley; Maria C. Caldeira; Ian Donohue; Maren Dubbert; Anne Ebeling; Nico Eisenhauer; Anu Eskelinen; Alain Finn; Tobias Gebauer; et al. (Global Change Biology, 2021)
Droughts can strongly affect grassland productivity and biodiversity, but responses differ widely. Nutrient availability may be a critical factor explaining this variation, but is often ignored in analyses of drought responses. Here, we used a standardized nutrient addition experiment covering 10 European grasslands to test if full‐factorial nitrogen, phosphorus, and potassium addition affected plant community responses to inter‐annual variation in drought stress and to the extreme summer drought of 2018 in Europe. We found that nutrient addition amplified detrimental drought effects on community aboveground biomass production. Drought effects also differed between functional groups, with a negative effect on graminoid but not forb biomass production. Our results imply that eutrophication in grasslands, which promotes dominance of drought‐sensitive graminoids over forbs, amplifies detrimental drought effects. In terms of climate change adaptation, agricultural management would benefit from taking into account differential drought impacts on fertilized versus unfertilized grasslands, which differ in ecosystem services they provide to society.

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Fine mapping of HIV-1 Nef-epitopes by monoclonal antibodies - H. Siakkou; S. Jahn; N. Kienzle; R. Ulrich; C. Grtzinger; T. Schneider; B. Kohleisen; G. Pauli; R. Spohn; G. Jung; N. Mller-Lantzsch; D. H. Krger (Archives of Virology, 1993)